Hydrobiology - MDPI (MDPI, 2026)
Hydrobiology is an international, peer-reviewed, open access journal on freshwater and marine biology, limnology, fisheries, oceanography, and aquatic ecology published quarterly online by MDPI.
Keywords: Hidrobiología; Limnología; Revistas depredadoras; Predatory journals